Answer:
Step-by-step explanation:
(a - b)(a + b) =a² - b²
(3x + 5)(3x -5) =(3x)² - 5² = 9x² - 25
(x +2)(x+2) = (x+ 2)² = x²+ 2*2*x+2² = x² + 4x + 4
(x+2)(3x -5 ) = x*3x - 5*x +2*3x +2*(-5)
= 3x² -5x +6x -10
= 3x² + x - 10
[tex]\frac{2*(3x+5)}{x+2}-\frac{5(x+2)}{3x-5}=3\\\\\frac{2*(3x+5)*(3x-5)}{(x+2)(3x-5)}-\frac{5*(x+2)(x+2)}{(3x-5)(x+2)}=3\\\\\frac{2*(9x^{2}-25)-5(x^{2}+4x+4)}{(3x-5)(x+2)}=3[/tex]
[tex]\frac{18x^{2}-25-5x^{2}-20x-20}{3x^{2}+x-10}=3\\\\\frac{18x^{2}-5x^{2}-20x - 25-20}{3x^{2}+x-10}=3\\\\[/tex]
13x² - 20x - 45 = 3*(3x² + x - 10)
13x² - 20x - 45 =9x² + 3x - 30
13x² - 9x² -20x - 3x - 45 + 30 = 0
4x² - 23x - 15 = 0